Estudio de satisfacción de egresados de Administración Pública de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, período 2017-2019 - Lucas Aveiga, Karen Estefanía (2022)
The research aimed to evaluate the satisfaction of Public Administration graduates of the ESPAM MFL period 2017-2019, for the improvement of professional training processes. The study was developed in three stages: 1) diagnosis of the degree of satisfaction through the application of online surveys; 2) determination and definition of professional competencies through questions based on a Likert scale; 3) establishment of a plan for information management and follow-up to graduates that incorporated objectives, actions, indicators, means of verification, assumptions, deadlines and responsible parties. It was found that of the 21 of the 22 dimensions analyzed, a High level of satisfaction prevailed, only "salary" had a Moderate level of prevalence (48.5%; N=50). Confidentiality and reserve, and written and oral communication skills in the mother tongue were identified as the professional competencies most developed by the target group (71.8% and 66.0%, respectively). The established plan integrates a total of 4 objectives and 11 specific actions, framed in timeframes ranging from six to twelve months. It is concluded that the satisfaction study contributes to the Public Administration career, so that it can effectively manage the teaching programs, strengthen the students' competencies and optimize the processes of information and follow-up to graduates; and this allowed corroborating the idea of the research.